2019
DOI: 10.1128/aac.02431-18
|View full text |Cite
|
Sign up to set email alerts
|

Results from the China Antimicrobial Surveillance Network (CHINET) in 2017 of the In Vitro Activities of Ceftazidime-Avibactam and Ceftolozane-Tazobactam against Clinical Isolates of Enterobacteriaceae and Pseudomonas aeruginosa

Abstract: The in vitro activities of ceftazidime-avibactam (CZA), ceftolozanetazobactam (C-T), and comparators were determined for 1,774 isolates of Enterobacteriaceae and 524 isolates of Pseudomonas aeruginosa collected by 30 medical centers from the China Antimicrobial Surveillance Network (CHINET) in 2017. Antimicrobial susceptibility testing was performed by the CLSI broth microdilution method, and bla KPC and bla NDM were detected by PCR for all carbapenemresistant Enterobacteriaceae (CRE). Ceftazidime-avibactam de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 21 publications
5
66
3
Order By: Relevance
“…Two recent multicenter studies also showed that the vitro activity of CZA against CRKP in adults is high. 25,26 Any decrease in susceptibility to CZA, a novel agent with minimal previous clinical use even in adults, is of concern. To the best of our knowledge, this is the first report of the vitro activity of CZA-resistant CRKP isolated from neonates, including premature neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent multicenter studies also showed that the vitro activity of CZA against CRKP in adults is high. 25,26 Any decrease in susceptibility to CZA, a novel agent with minimal previous clinical use even in adults, is of concern. To the best of our knowledge, this is the first report of the vitro activity of CZA-resistant CRKP isolated from neonates, including premature neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CAZ/AVI against carbapenem-resistant K. pneumoniae strains has been shown to be very effective to provide a higher clinical cure rate and survival rate in China, the United States, and other European countries. [23][24][25][26] However, increased reports of CAZ/AVI resistance in carbapenem-resistant K. pneumoniae, regardless of prior exposure, is a matter of concern. [27][28][29] A national research about CAZ/AVI resistance in China revealed that MBL production, bla KPC-2 point mutation and high KPC expression played an important role in CAZ/AVI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftolozane-tazobactam's strength resides in its potent activity against P. aeruginosa, including multi-drug resistant (MDR) strains with 90-98% of contemporary isolates testing susceptible [17][18][19][20][21][22][23][24][25][26]. Moreover, ceftolozane-tazobactam is a potential carbapenem-sparing treatment regimen against ESBL-producing Enterobacteriaceae [18][19][20][21][22]24]. Ceftolozanetazobactam's activity against ESBL-producing K. pneumoniae as revealed through susceptibility testing is largely lacking [20,21,24,27]; however, in spite of these in vitro results, clinical cure rates are high [28].…”
Section: Ceftolozane-tazobactammentioning
confidence: 99%
“…Moreover, ceftolozane-tazobactam is a potential carbapenem-sparing treatment regimen against ESBL-producing Enterobacteriaceae [18][19][20][21][22]24]. Ceftolozanetazobactam's activity against ESBL-producing K. pneumoniae as revealed through susceptibility testing is largely lacking [20,21,24,27]; however, in spite of these in vitro results, clinical cure rates are high [28]. Conversely, the combination is mostly ineffective against Enterobacteriaceae with serine carbapenemases [29][30][31].…”
Section: Ceftolozane-tazobactammentioning
confidence: 99%